(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Liquefied petroleum gas LPG is a good alternative to gasoline fuel. It has emerged as a solution to the deteriorating urban air quality problem especially in an oil country like Iraq. Computational model is used for parametric study of spark ignition engine works on Iraqi fuel (gasoline or LPG). Transient one dimensional continuity, momentum and energy equations are solved by two – step Lax wender off (Ritchmyer) approach to evaluate brake specific fuel consumption BSFC, brake power, brake thermal efficiency, volumetric efficiency, air fuel ratio, in cylinder pressure and exhaust gas temperature. Results revealed that LPG fuel improves BSFC by 3.11% as a maximum compare to gasoline for 10 kW brake power and 9.9:1 compression ratio. The maximum cylinder pressures predicted for LPG are lower than that for gasoline fuel. The volumetric efficiency was 76.8 % for engine works with, LPG at compression ratio 9.9:1. While that for gasoline was 85.9%. The equivalence ratio is higher for gasoline than that for LPG, since the first required higher air-fuel ratio for combustion. The reported maximum exhaust gas temperature for LPG is 706oC, while that for gasoline is 741.4oC.